The Impact of Community Based Health Insurance Schemes on Out-of-Pocket Healthcare Spending : Evidence from Rwanda - Woldemichael, Andinet; Gurara, Daniel; Shimeles, Abebe (Washington, D.C. : International Monetary Fund, 2019)
Achieving universal health coverage, including financial risk protection and access to quality essential health-care services, is one of the main Sustainable Development Goals. In low-income countries, innovative and affordable health financing systems are key to realize these goals. This paper assesses the impacts of Community-Based Health Insurance Scheme in Rwanda on health-related financial risks using a nationally representative household survey data collected over a ten-year period. We find that the scheme significantly reduce annual per capita out-of-pocket spending by about 3,600 Rwandan Franc (about USD 12) or about 83 percent of average per capita healthcare expenditure compared to the baseline level in 2000.The impacts however favor the rich as compared to the poor. The program also reduces the incidence of catastrophic healthcare spending significantly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet